Implementasi SQC (Statistical Quality Control) dalam Proses Pascapanen Tebu di PG. Madukismo - Figa Mahira; Hety Handayani Hidayat (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
PG. Madukismo is a company engaged in the processing of sugarcane into sugar. In the sugar production process, in terms of raw materials, there are still mixtures or components of sugarcane that are not needed and desired. This is caused by external and internal factors of the company which will certainly affect the quality of the products produced. The purpose of this study is to identify the quality of sugarcane by using Statistical Quality Control (SQC) analysis. This study uses the seven tools method for quality control with the results of the research showing the cause of dirty sugarcane is around 14.44% of the total received sugarcane  due to other components besides sugarcane that are needed such as dry leaves, roots, soil and etc. It was found that the types of quality problems that occurred in sugarcane received by the factory in 2021 were gross 1 (K1) with a percentage of 82.6%, gross 2 (K2) with a percentage of 6.5% and gross 3 (K3) with a percentage of 10.9%. The quality problem of sugarcane received by the factory is caused by human factors (workers), materials, methods, machines and the environment.